Buckling of steel tanks under measured settlement based on Poisson curve prediction model. (September 2016) - Fan, Haigui; Chen, Zhiping; Shen, Jianmin; Cheng, Jian; Chen, Dingyue; Jiao, Peng
Abstract: Buckling behavior of large steel tanks under measured settlement has been researched and analyzed in this paper. The settlement prediction model based on Poisson curve is established by applying least square principle and Lagrange quadratic interpolation. Settlement of each measuring point at any time can be obtained applying this prediction model. The discrete settlement data at any time beneath the tank wall is transformed into global settlement expression distributed in the circumferential direction by using the method of Fourier series expansion. Settlement variation with time beneath the tank wall is predicted accurately then. Based on the predicted settlement beneath the tank wall at any time, bucking behavior of the tank is researched by numerical simulation method and the critical buckling time of the tank is predicted. Hydrostatic pressures are applied to inner surface of the tank wall to research the buckling behavior of the tank with different liquid storage. The present method is applied to a fixed roof tank and result shows that the tank wall presents stable linear variation under settlement in initial stage. As time and settlement increase, a typical snap-through buckling occurs to the tank wall, which indicates that the buckling analysis method presented in this paper can be used to predict the buckling behavior of the tank effectively. Buckling behavior analysis of a floating roof tank with the same size and under the same settlement with the fixed roof tank is also made. It indicates that compared to the buckling of fixed roof tanks, the radial displacement on the top of the floating roof tank wall is regarded as the controlling factor to determine the tank failure. Highlights: Settlement beneath tank wall is predicted by Poisson curve prediction model. Bucking behavior of a fixed roof tank at different times under settlement is analyzed. The critical buckling time of the tank under settlement is predicted. Effects of liquid on the buckling of the tank under settlement is analyzed. Analysis of a same size floating roof tank is compared with the fixed roof tank.